The Five Domains Model for the evaluation of animal welfare: case of an African lion (Panthera leo) - Álvarez Chavarría, Paula (2023)
The Five Domains Model is a tool to evaluate the state of animal welfare in captivity through the monitoring of subjective, both negative and positive experiences. There are four physical and functional domains: nutrition, environment, health and behavior; while the fifth domain called mental state is an affective experience. In cases where all domains reach an optimal state, the animal is said to be in good health. In this report, The Five Domains Model was applied to evaluate the management of animal welfare of a resident lion of the Simón Bolívar National Zoological Park and Botanical Garden, Costa Rica, during osteoarthritis treatment received between May and December 2016.